Tourism and Hospitality Essentials (THE) Journal, Vol.II, No.1, 2012 - 245 ANALISIS FAKTOR-FAKTOR PENDORONG MOTIVASI WISATAWAN NUSANTARA TERHADAP KEPUTUSAN BERKUNJUNG KE KEBUN RAYA BOGOR (Survei Pada Wisatawan Nusantara yang Berkunjung ke Kebun Raya Bogor) - Hermansyah, Danu; Waluya, Bagja (Universitas Pendidikan Indonesia, 2012)
Bogor Botanical Gardens (KRB), has a tourist attraction (DTW) in the form of natural beauty and have never experienced a change from the previous hundred years. Tourists (wisnus) contributed 97% of the number of visits, but the number of visits wisnus from year to year decline, with the known factors that drive wisnus who visited the BBG, BBG manager can know wisnus needs when traveling, need for such wisnus can be met and can be marketed through various marketing programs. Based background, then the formulation of this study as follows: 1) Describing the factors driving wisnus to KRB. 2) How would the decision to visit KRB. 3) How does the influence of the push factors driving the decision wisnus to visit KRB. This type of study is a deskritif and verifikatif, so the method used is the explanatory survey. Sampling technique is systematic random sampling with a sample size of 100 respondents. Data analysis technique used is of the Path Analysis with SPSS 18.0 software. The results showed that the response domestic tourists of push factors Driving Been Against Decision to KRB is generally considered quite high. Factors that gets the highest ratings of the relaxation factor of 0.227 or 22.7%, because KRB has a very beautiful natural setting and have the cool air that makes wisnus want to make a visit to the KRB in order to refresh themselves both physically and mentally, while the response factor wisnus about family and friend togetherness undervalued. Domestic tourists responses to the decision in general been quite high in value. Factors that gets the highest ratings on the choice of brands for 20.74%. This is because KRB has a very good name in the minds of domestic tourists regarding both the popularity and uniqueness tourist attraction owned by KRB, and the introduction of the tourist attraction offered by KRB While assessors are the lowest is in the choice of products and services that is equal to 19.3%. Verificative results indicate that the push factors driving have a significant high value in influencing the decision to visit that is equal to 82.43%. This means that the better the factors that drive the more powerful it wisnus decision to KRB, there is a sub-variable that does not have a significant influence is relaxation. This is because every wisnus who visited the KRB aims to relax but now will make a visit to the KRB wisnus obstacles by traffic jam that often occur in the city of Bogor, the heavy rains that often inhibits wisnus to visit and day trips to the KRB and the unavailability of the area parking on the weekend.